THE SPECIFICS OF TEACHING A FOREIGN LANGUAGE TO STUDENTS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
The distinctive features of English language teaching are its communicative focus, integrative nature (learning culture through language), and use of a student-centered approach. Key aspects include the development of the four skills (speaking, listening, reading, and writing), the use of authentic materials, consideration of student goals (ESP, business), and the use of interactive methods to overcome language barriers.